The influence of health education about the true position of breastfeeding for post partum mothers in the Pepe Village, Indonesia - Fauziyatun Nisa; Shrimarti Rukmini Devi (Journal of Public Health in Africa, 2019)
Breastfeeding is a natural process in which pregnant mothers will be breastfeeding to help their babies stay healthy. However, several factors can interfere with appropriate breastfeeding, such as family income, mothers’ knowledge about breastfeeding and supportive environment. This study aimed to identify the effect of health education on maternal behavior in breastfeeding techniques. The design of this study was one-group pre-post design. 122 postpartum mothers were chosen as samples in this study by simple random sampling technique. Data was collected using observation sheets, and then analyzed by using Wilcoxon signed rank test with a significance level of α = 0.05. The results showed that there was a significant effect of health education on maternal behavior in breastfeeding techniques with a result of p value of 0.000. It is hoped that all postpartum mothers can follow breastfeeding techniques with a proper positioning, ensure proper latching on to the nipples, so breastfeeding can be a comfortable and pain-free experience both for mothers and the babies.